Breast Cancer Perceptions and the Related Factors in Women Referred to Health Centers in Tabriz, Northern Iran - Elham Seyedkanani; Leila Sheikhnezhad; Sepideh Soltani; Mojgan Mirghafourvand; Mina Hosseinzadeh (نشریه پرستاری ایران)
Background & Aims Breast cancer is the most prevalent cancer among women, with negative impacts on their health and well-being. Women’s perceptions of breast cancer can affect their preventive and screening behaviors. This study aims to survey the perceptions of breast cancer and identify the associated factors among women attending healthcare centers in Tabriz, north of Iran. Materials & Methods The descriptive cross-sectional study was conducted on 372 women aged >40 years referred to healthcare centers in Tabriz city from December 2022 to March 2023. A cluster random sampling method was employed. Data were collected using a sociodemographic form and Taylan et al.’s breast cancer perception scale (BCPS). Descriptive statistics, Pearson correlation test, independent t-test, ANOVA, and general linear model were utilized for data analysis in SPSS software, version 16. Results The mean total score of BCPS was 65.04±8.60. The perceived fear dimension had the lowest mean score (8.27±4.02). A significant difference was observed in the BCPS score based on the woman’s educational level (P<0.001), the husband’s educational level (P=0.002), the number of children (P=0.04), and the history of a benign change in women’s breast (P<0.001). Based on the regression analysis, women’s educational level (B=-0.13, 95%CI=0.02-0.24, P=0.018) and number of children (P=0.048, B=-0.038, CI=-0.003-0.79) were the predictors of breast cancer perception. Conclusion The women in Tabriz City have a relatively low level of breast cancer perception, highlighting the need for targeted educational interventions to improve their knowledge and mitigate their fear. More educational programs are needed for women with low educational levels and a high number of children in health centers to promote their breast cancer perceptions and screening outcomes.